1983
DOI: 10.1007/bf00914244
|View full text |Cite
|
Sign up to set email alerts
|

Learning through observation: The effects of peer modeling on acquisition and generalization in autistic children

Abstract: The purpose of this study was to systematically determine whether low-functioning autistic children [MA of approximately half of their CA or less] could learn through observation by the use of a peer modeling procedure. Since modeling is less structured than traditional one-on-one procedures, it was also thought that modeling might facilitate subsequent generalization of tasks learned through observation. Four autistic children were taught two receptive labeling tasks. One task was taught by a traditional tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
3

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 27 publications
3
45
0
3
Order By: Relevance
“…Interestingly, modeling is also effective for children with "abnormal" cognitive development. Such studies have shown that peer modeling, but not adult modeling, is effective for educable mentally retarded children (e.g., Barry and Overman 1977) and autistic children (e.g., Charlop et al 1983). Bandura (1986) has also noted the important mediating role of prior knowledge in learning from modeling examples.…”
Section: For What Kinds Of Learners Is Example-based Learning Effective?mentioning
confidence: 99%
“…Interestingly, modeling is also effective for children with "abnormal" cognitive development. Such studies have shown that peer modeling, but not adult modeling, is effective for educable mentally retarded children (e.g., Barry and Overman 1977) and autistic children (e.g., Charlop et al 1983). Bandura (1986) has also noted the important mediating role of prior knowledge in learning from modeling examples.…”
Section: For What Kinds Of Learners Is Example-based Learning Effective?mentioning
confidence: 99%
“…A strong case has been made for peerinvolved procedures such as modeling, prompting, and cross-age tutoring (e.g., Charlop, Schreibman, & Tryon, 1983;Egel, Richman, & Koegel, 1981;Kamps, Locke, Delquadri, & Hall, 1989). In addition, various investigations have demonstrated peer strategies to be an appropriate vehicle for improving social skills and development.…”
mentioning
confidence: 99%
“…Specifically, a time delay procedure (Charlop et al, 1985;Halle, Marshall, & Spradlin, 1979) (Charlop, Schreibman, & Tryon, 1983;Egel, Richman, & Koegel, 1981) were used in an attempt to teach the children to spontaneously vocalize "I like you" or "I love you" in response to a hug by a familiar person or their mother, respectively. We employed the definition of spontaneity used in Charlop et al (1985): "a verbal response to a nonverbal discriminative stimulus in the absence of a verbal discriminative stimulus."…”
Section: Increasing Autistic Children's Spontaneous Verbalizations Ofmentioning
confidence: 99%